O tipo como recurso de revisão historiográfica da arquitetura moderna: uma análise da residência José Félix Louza - Almeida, Mayra de Paula Nascimento (2019)
This research aims to test an alternative explanation to the linear “diffusion-reception” historical narrative for the modern architecture in Brazil. For that, it uses “type” as an instrument of analysis for José Félix Louza’s House, a 1950’ David Libeskind project in the city of Goiânia. The investigation presents the construction process of a hegemonic narrative that attributes the “irradiator” role to central big cities (such as Rio de Janeiro e São Paulo) and the “popularization” role to the peripheric productions, such as the one in Goiânia. Retaking the evolution of the type concept in the discipline, this research explains its meaning as: part of the existent architecture culture in a certain historical moment, the result of a collectivity needs and enabled by its technique. Starting from a glance on the project, the first moment scrutinizes the houses’s key elements through tipos settoriales: the home-courtyard; the tripartition organization of nineteenth century; the sliding planes and its textures. In a second moment, each one of these types is observed in the concerning context as an architectural historic process . This process reveals that the types of Jose Félix Louza’s House are also tipos integratos, in other words, they are linked to the place where they are inserted, therefore, they are not plain copies of paradigmatic examples.